ON THE IMPACT OF DIFFERENT SYSTEM STRATEGIES ON THE MATERIAL PERFORMANCE OF SELECTIVE LASER MELTING- MANUFACTURED TI6AL4V COMPONENTS - Dimitrov, Dimitri; Becker, Thorsten Hermann; Yadroitsev, Igor; Booysen, Gerry (Stellenbosch University Library and Information Service : The South African Journal of Industrial Engineering, 2016)
Selective Laser Melting (SLM) is a powder-based additive manufacturing process that has gained substantial interest in recent years due to its feasibility of producing geometrically- complex metallic components for end-use in various industries, with or without post-treatment procedures. This paper presents recent research undertaken on different scanning strategies and process parameters with the purpose of providing an overview of the achievable material performance of Ti6Al4V components, and comparing its properties with the conventionally-produced parts. In order to understand their output, differences in the building strategies of the systems studied are analysed, and their influence on the resulting mechanical and metallurgical properties is highlighted.
Published Article
Keywords: Selective Laser Melting; Titanium; Microstructure; Material Properties